The application of risk analysis to the project appraisal of stingless bee farming in Malaysia for sustainability - Abdurofi, Ilmas; Ismail, Mohd Mansor; Ismail, Normaz Wana (Universiti Malaysia Terengganu, 2021)
Before implementing the massive production of stingless honeybees in order to increase honey yields, the viability and future sustainability of the stingless bees project should be carefully appraised. The objective of this study is therefore to assess the financial projections and simulate the risk factors that may affect future growth projections of stingless bee farming. The study uses capital budgeting techniques and sensitivity analysis scenarios, tax obligation and tax incentives. The findings showed that the stingless bee farming project in Malaysia is financially viable, highly-profitable and can swiftly recover its initial investment. Specifically, the farms on the Peninsular have high projected cash earning capacity, while more efficient farming and less project risks are seen in the Sarawak region. Additionally, if tax obligations are imposed, all indicators of financial appraisal have shown to be still attractive and the results are more lucrative with the application of tax waivers. Furthermore, the project would not be impacted in the change of hive prices and labour costs, indeed the farm is economically sustainable. The main concern should be changes in selling price as these are a considerable drag on the future appraisal of the project.